Spatial Single Cell Profiling Using Imaging Mass Cytometry: Inflammatory Versus Penetrating Crohn's Disease - Lehmann, Malte; Weixler, Benjamin; Elezkurtaj, Sefer; Loddenkemper, Christopher; Atreya, Imke; Atreya, Raja; Bacher, Petra; Becker, Christoph; Bojarski, Christian; Britzen-Laurent, Nathalie; Bosch-Voskens, Caroline; Chang, Hyun Dong; et al. (Journal of Crohns & Colitis, 2024)
Background and Aims: Fistula formation is a major complication in Crohn's disease [CD] and the role of the immune cell compartment remains to be elucidated. Thus, we compared the immune cell compartment of CD fistula to inflammatory CD colitis using imaging mass cytometry [IMC] and immunofluorescence. Methods: A 36-marker panel including structural, functional, and lineage markers for use in IMC was established. This panel was applied to analyse paraffin-embedded CD fistula tract [n = 11], CD colitis [n = 10], and colon samples from non-inflamed controls [n = 12]. Computational methods for cell segmentation, dimensionality reduction, and cell type clustering were used to define cell populations for cell frequency, marker distribution, and spatial neighbourhood analysis. Multiplex immunofluorescence was used for higher resolution spatial analysis. Results: Analysis of cell frequencies in CD fistulas compared to CD colitis and control colonic samples revealed a significant increase in neutrophils, effector cytotoxic T cells, and inflammatory macrophages in CD fistula samples, whereas regulatory T cells were decreased. Neutrophils in CD fistula expressed significantly more matrix metalloproteinase 9 [MMP9], correlating with extracellular matrix remodelling. Neighbourhood analysis revealed a strong association between MMP9+ neutrophils and effector cytotoxic T cells in both CD fistulas and colitis. Conclusions: This study presents the first highly multiplexed single cell analysis of the immune cell compartment of CD fistulas and their spatial context. It links immune cell dynamics, particularly MMP9+ neutrophils, to extracellular matrix remodelling in CD fistulas, offering insights into the complex network of cellular interactions and potential therapeutic targets for CD complications.
CRIS-Team Scopus Importer:2024-09-13
Keywords: fistula; imaging mass cytometry; Penetrating Crohn's disease